Silencing of S100A16 in Cervical Cancer Cells Inhibits Cancer Cell Growth by Inducing Autophagy via PI3K/AKT/ mTOR Signaling Pathway - Zhang, Haibin; Xing, Wenhu; Li, Yufeng; Xu, Xianyun (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Cervical Cancer (CC) ranks among the top 3 leading malignancies that affect the female reproductive system. This research focused on examining the impact of S100A16 silencing in HeLa and CaSki cells, alongside exploring the underlying molecular mechanisms involved. Materials and Methods: Cells were treated with si-S100A16 for a specific duration, as well as the impacts on migration, cell proliferation, cell cycle progression, apoptosis, as well as various signaling pathways were assessed. Additionally, in vivo tumor xenograft assays were carried out to evaluate the influence of S100A16 on tumor development. Results: The data revealed a significant rise in S100A16 expression in cervical cancer cells. Silencing S100A16 caused a considerable decrease in cell proliferation, hindered migration, enhanced apoptosis, and inhibited the PI3K/Akt/mTOR signaling pathway, while simultaneously inducing autophagy. In HeLa tumor-bearing mice, S100A16 silencing demonstrated robust anti-tumor effects by increasing the expression of autophagy-related proteins LC3II/I and Beclin1, simultaneously reducing p62 expression. Furthermore, levels of phosphorylated PI3K, Akt, as well as mTOR were markedly decreased. Conclusion: The study demonstrated that S100A16 silencing impairs the PI3K/AKT/mTOR signaling pathway, consequently enhancing cellular autophagy. These results underscore the anti-tumor potential of S100A16 silencing in CC cells, likely due to its suppression of the PI3K/AKT/mTOR pathway, which enhances autophagy.
Keywords: Autophagy; Cervical cancer; PI3K/AKT/Mtor; S100A16